Entomocidal ability of native strains Beauveria sp. on Schistocerca piceifrons peruviana (Lynch Arribalzaga, 1903) - Pariona, Nicolaza (2007)
Four strains of Beauveria sp. (ABvPr11, ABvPr8, ABvPr3, ABvSr4), that were found in the locust Schistocerca piceifrons peruviana from Huamanga, Ayacucho, Peru, were isolated and morphologically characterized. Entomicidal activities of four strains were evaluated on the locust. Results showed that all the strains producing 100% mortality when using solutions of 108 conidias/mL. The time for 100% mortalities of the strains ABvPr11, ABvPr8, ABvSr4 y ABvPr3 were 12, 14, 14 y 16 days respectively. In the tenth day significant differences were observed between the mortality of the strains ABvPr11 (90%) and ABvSr4 (74%), ABvPr8 (72%), ABvPr3 (64,6%). Lethality time was determinate for the 50% (TL50) of the locust population: ranging from 8,38 to 9,16 days. Lethality time for the 80% (TL80) ranged from 9,6 to 11,5 days. The ABvPr11 strain presented the highest biocidal activity for the Schistocerca piceifrons peruviana L.A.